KEY ASPECTS OF ENSURING THE QUALITY AND SAFETY OF FOOD PRODUCTS IN THE RESTAURANT BUSINESS (Development Service Industry Management, 2023)
The article argues that food safety is a key factor in the successful functioning of restaurant business establishments, and the quality of food products directly affects the success of the business. The main provisions of the regulatory and legal support of the HACCP system in Ukraine are clarified. The theoretical aspects of the system of quality management of products and services in the restaurant business are analyzed, taking into account the works of domestic and foreign scientists and specialists on ways to improve the quality of products and services. On the basis of the study, it is determined that an effective system for managing the quality of products and services in the restaurant business should include a set of HACCP principles, the application of which provides enterprises with a number of advantages. It is noted that the HACCP system covers product safety parameters at all stages of its life cycle - from obtaining raw materials to consuming finished products. In turn, it is emphasized that the prerequisite programs also cover other systems, such as: management of purchased materials; supplier approval programs; traceability systems for raw materials and final products; receipt, storage and distribution systems; product labeling; management of production equipment for its suitability; personnel training, etc.
Keywords: quality; safety; restaurant business; food products; prerequisite programs; quality management; HACCP